Pharmacogenomics of Hypersensitivity to Non-steroidal Anti-inflammatory Drugs - Trinh, Hoang Kim Tu; Pham, Le Duy; Le, Kieu Minh; Park, Hae-Sim (Frontiers in Genetics, 2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) are extensively prescribed in daily clinical practice. NSAIDs are the main cause of drug hypersensitivity reactions all over the world. The inhibition of cyclooxygenase enzymes by NSAIDs can perpetuate arachidonic acid metabolism, shunting to the 5-lipoxygenase pathway and its downstream inflammatory process. Clinical phenotypes of NSAID hypersensitivity are diverse and can be classified into cross-reactive or selective responses. Efforts have been made to understand pathogenic mechanisms, in which, genetic and epigenetic backgrounds are implicated in various processes of NSAID-induced hypersensitivity reactions. Although there were some similarities among patients, several genetic polymorphisms are distinct in those exhibiting respiratory or cutaneous symptoms. Moreover, the expression levels, as well as the methylation status of genes related to immune responses were demonstrated to be involved in NSAID-induced hypersensitivity reactions. There is still a lack of data on delayed type reactions. Further studies with a larger sample size, which integrate different genetic pathways, can help overcome current limitations of genetic/epigenetic studies, and provide valuable information on NSAID hypersensitivity reactions.